Survival benefit of hepatectomy after complete or partial response to conversion therapy in unresectable hepatocellular carcinoma (GUIDANCE003): a multi-center study - Yang, Da-Long; Peng, Ning; Nong, Jun-Liang; Chen, Kang; Su, Ze; Yu, Ya-Qun; Ye, Lin; Zeng, Fan-Jian; Liu, Shao-Ping; Yan, Yi-He; Wang, Xue-Yao; Yao, Hong-Bing; et al. (Liver cancer (Basel ), 2025)
Introduction: The uncertainty exists regarding whether hepatectomy enhances the prognosis for initially unresectable hepatocellular carcinoma (HCC) that becomes resectable subsequent to conversion therapy. This study conducted a comparative analysis of survival rates between patients who underwent hepatectomy and those who did not, following complete or partial response to conversion therapy. Methods: This retrospective study examined 300 patients with HCC who underwent hepatectomy following conversion therapy, along with 265 non-surgical control subjects (215 receiving loco-regional/systemic therapy and 50 under active surveillance) across 20 Chinese medical centers from 2019 to 2023. The primary outcomes assessed included overall survival (OS), event-free survival (EFS), recurrence-free survival, and the rate of complete pathologic response. Results: Hepatectomy was associated with significantly better OS than loco-regional or systemic therapy or active surveillance (The 3-year OS rates were 79.9% and 58.5%, respectively, p < 0.001) but comparable EFS (median: 40.6 vs 33.4 months, p = 0.403). These results were confirmed after analyzing subgroups matched to each other based on propensity scoring. Among patients who underwent hepatectomy, those who responded completely to conversion therapy showed significantly better OS than those who responded partially (HR 0.40, 95%CI 0.21-0.75) as well as significantly better EFS (HR 0.45, 95%CI 0.29-0.70). Among patients who did not undergo hepatectomy, overall and EFS were comparable between those who responded partially and those who responded completely to conversion therapy. Additionally, loco-regional or systemic therapy showed significantly better results in terms of overall and EFS compared to active surveillance. Of the patients who underwent hepatectomy, 116 (38.7%) showed complete pathologic response. In patients underwent hepatectomy, those who experienced complete pathologic response showed significantly better OS than those who did not (HR 0.34, 95%CI 0.18-0.65) as well as significantly better recurrence-free survival (HR 0.38, 95%CI 0.25-0.59). Conclusions: Hepatectomy can provide significant OS benefit to patients with initially unresectable HCC that responds partially or completely to conversion therapy.